2018
DOI: 10.25100/cm.v49i1.3155
|View full text |Cite
|
Sign up to set email alerts
|

Calidad del certificado de defunción en Colombia

Abstract: Objective: To evaluate the quality of the certification of general death and cancer in Colombia.Methods: Validity indicators were described for each province and the cities of Bogotá, Cali, Manizales, Pasto and Bucaramanga. A factorial analysis of principal components was carried out in order to identify non-obvious relationships.Results: Were analyzed 984,159 deaths, among them there were 164,542 deaths due to cancer. 93.7% of the general mortality was well certified. The predominant errors were signs, sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
0
26
0
12
Order By: Relevance
“…A recent study has shown that general accuracy of vital statistics has worsened in Argentina, Colombia and México during the period 2000-2011, 20 but is countered by one Colombian study that reported the reasonable quality of death certification for cancer deaths. 21 The declining lung cancer mortality rates observed among males in the seven countries with mortality data, accompanied by rising rates among females, probably reflects the historical and gender-specific smoking profiles, with smoking prevalence among men earlier and falling versus a later and rising smoking uptake among women. Unfortu- Bray F, Piñeros M and breast cancer incidence, given precursor lesions are not the target of the intervention.…”
Section: 23mentioning
confidence: 99%
“…A recent study has shown that general accuracy of vital statistics has worsened in Argentina, Colombia and México during the period 2000-2011, 20 but is countered by one Colombian study that reported the reasonable quality of death certification for cancer deaths. 21 The declining lung cancer mortality rates observed among males in the seven countries with mortality data, accompanied by rising rates among females, probably reflects the historical and gender-specific smoking profiles, with smoking prevalence among men earlier and falling versus a later and rising smoking uptake among women. Unfortu- Bray F, Piñeros M and breast cancer incidence, given precursor lesions are not the target of the intervention.…”
Section: 23mentioning
confidence: 99%
“…The incidence / mortality ratio of the period of interest of each regional RCPob is incorporated into a mathematical model that uses this information and the mortality observed in each department as inputs to estimate the departmental and national incidence 3 , 11 . The validity of the estimates depends on the quality of the information and also on the accurate quality of the certification of general mortality and cancer in Colombia and the coverage of the certification is close to 100% 12 .…”
Section: Introductionmentioning
confidence: 99%
“…La razón incidencia/mortalidad del periodo de interés de cada RCPob regional, se incorpora en un modelo matemático que utiliza esta información y la mortalidad observada en cada departamento como insumos para estimar la incidencia departamental y nacional 3 , 11 . La validez de las estimaciones depende de la calidad de la información, y la calidad de la certificación de la mortalidad general y por cáncer en Colombia es buena y la cobertura de la certificación es cercana al 100% 12 .…”
Section: Introductionunclassified
“…Brazil recorded more than 1.31 million deaths in 2017, accounting for over 96% of all deaths; of these deaths, 36.5% were garbage codes (GCs). (3)(4)(5) GCs are a classic indicator of the quality of health information systems, (6)(7)(8) and have been used as an indicator of the level of comprehensiveness and specificity of information on death certificates. (9) It is not uncommon for records to not specify a valid COD, requiring in-field collection of supplementary information.…”
Section: Introductionmentioning
confidence: 99%